A Correlational Study of UK Press Climate Change Discourses and Explicit CSR Reporting: A British Petroleum (BP) case study - Webb, J A S (2009)
The growing literature within the arena of corporate social responsibility (CSR) has broadened both the view and importance of corporate sustainability. In this respect environmental issues remain at the forefront when thinking about social responsibility. For example, the focus of the research in this thesis, is the issue of climate change. For a growing number of years the public has been bombarded with ‘doomsday’ scenarios and mixed messages regarding both the imminent impact and cost of climate change. Perhaps this is due to the media being a major outlet and source of information, and the increasing number of discourses revolving around climate change. Due to the relative size and power of media, the discourses can prove instrumental in framing the general opinion and strategy of major organisations. Using this rationale, coupled with the literature regarding the use of CSR as an explicit reputational management tool, organisations may be paying closer attention to these media discourses. The aim of this research project is to study these phenomena and whether a specific corporation, British Petroleum (BP), has been affected by the persuasive impact of both the media and the nonmarket environment in their explicit reporting. The climate change discourse analysis on the media and the case study of BP, has investigated the relationship between media discourses and explicit CSR reporting. By using this approach the objective is to understand the reactive and/or proactive nature of corporate reporting.